Effectiveness of advance care planning programmes in improving end-of-life outcomes for individuals with dementia and their caregivers in nursing homes: protocol for a systematic review and meta-analysis - Chih-Cheng Lai; Yu-Tai Lo; Yi-Jhen Chen; Jheng-Yan Wu (BMJ Open)
Introduction With advances in medicine and the resultant increased ageing population, dementia, including Alzheimer’s disease, has become a leading cause of death in individuals aged over 65 years in nursing homes. The unpredictable trajectory of the disease, marked by cognitive and functional decline, necessitates intensive healthcare and poses challenges to end-of-life (EoL) care decisions, particularly because majority of the affected individuals become unable to make their own decisions. This highlights the importance of advance care planning (ACP) programmes that enable individuals with dementia to define and communicate their EoL care decisions in advance. In this systematic review and meta-analysis, we aim to evaluate the effectiveness of ACP in nursing homes for patients with dementia and their caregivers.Methods and analysis This systematic review and meta-analysis will include randomised controlled trials (RCTs) and observational studies that evaluate the effectiveness of ACP programmes in improving EoL outcomes in individuals with dementia and their caregivers in nursing homes. EoL outcomes include (1) quality of life; (2) caregiver satisfaction; (3) advance directives completion rate, which refers to the proportion of individuals with completed, documented EoL care preferences; (4) uptake of ACP discussion indicating the frequency or occurrence of these discussions between healthcare providers, patients and/or family members; and (5) comfort in the last week of life. Studies will be retrieved from PubMed, Embase, Cochrane Library and ClinicalTrials.gov between their inception and 31 January 2024. Eligible articles will be selected according to prespecified inclusion and exclusion criteria. The quality of the included articles will be assessed using the Cochrane risk-of-bias tool 2.0 for RCTs and risk of bias in non-randomised studies of interventions for observational studies. The certainty of evidence will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation framework. Publication bias will be assessed using a funnel plot and Egger’s test to detect any asymmetry in the distribution of effect sizes across studies. Sensitivity and subgroup analyses will be conducted to address heterogeneity.Ethics and dissemination Ethics approval was not required for this systematic review and meta-analysis, as it involves the synthesis of existing literature without direct data collection or patient participation. The results of this study will be compiled into a detailed report, which will be submitted for publication in a peer-reviewed journal. Additionally, the findings will be shared with academic partners, healthcare professionals and organisations involved in dementia care, as well as policymakers and stakeholders in the field of long-term care for individuals with dementia.PROSPERO registration number CRD42023489126.